Polluters and abaters - Alain-Désiré Nimubona; Bernard Sinclair-Desgagné (Fondazione Eni Enrico Mattei (FEEM), 2010)
To comply with laws, regulations and social demands, polluting firms increasingly purchase the needed means from specialized suppliers. This paper analyzes this relatively recent phenomenon. We show how environmental regulation, the size of the output market, the elasticity of demand for abatement goods and services, and the fact that in-house and outsourced abatement expenses are substitutes or complements can influence a polluter's make-or-buy decision. Specific features of abatement outsourcing are highlighted, qualifications and refinements of the theory of vertical integration are then proposed, and some consequences for environmental policy are briefly discussed.
Keywords: L23; L24; Q52; 330; Eco-industry; Make-or-buy Decision; Outsourcing; Vertical Integration